Pengaruh Kualitas Produk Dan Harga Terhadap Penjualan di UD Beski Jaya - Rafikhein Novia Ayuanti; Athiy Dina Rosihana (Universitas Islam Kadiri, 2018)
Product quality and price are two factors that greatly affect sales. The sold products must be in a good quality, appealing appearance, worthy packaging, so consumers are consistently like to buy the products. Good product quality will encourage companies to maintain their business and be able to compete with other companies. This study aims to determine the effect to product quality and prices partially and simultaneously on sales at UD Beski Jaya, and to find out which variables have the most influence on sales. The analytical tools used are validity test, reliability test, classic assumption test, and multiple linear regression, correlation coefficient, determination coefficient T test and F test. The result show that there is a aprtial and simultaneous influence between product quality and price on sales. The primary suggestion for UD Beski Jaya is to evaluate its product in order to find out what products consumer want.